Establishing Trade Unionism in the Emerging Iron Ore Mining Industry in Western Australia's Pilbara Region, 1965–72. (November 2018) - Vassiley, Alexis
Abstract : By the 1970s, the Pilbara iron ore mining industry was a byword for union militancy. Yet when this industry was established in the 1960s, workers endured harsh conditions, unfettered managerial prerogative, low pay and there was little trade union organisation. To date, studies have concentrated on the period of union militancy, and little effort has been made to document and analyse the rise of trade unionism in this mining region of Western Australia. This article argues that industrial action by unionised and unionising mining workers in the period 1965–72 won serious improvements in pay and conditions, and eroded some of the power of management. Their demands were resisted fiercely by the iron ore companies. Much of the infrastructure of grassroots unionism – central to the exercise of "union power" in the 1970s and 1980s – was established during this period. This included networks of shop stewards, combined union committees and universal unionism. These struggles underpin and therefore contextualise the later union militancy, which has received more academic attention. This article draws on John Kelly's mobilisation theory to examine this period of working-class activity and union growth.